The Implementation of Lifelong Education in Non-formal Education - Taufik Rizki Sista; Farida Saifullah; Faridah Aryahiyyah (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
This paper is the result of library research with the focus of research is Out of School Education. The researcher used the data collection techniques from various backgrounds and off-school education. The purpose of this research is (1) To know the essence of lifelong education, (2) To know the implementation of lifelong education in Out of School Education, (3) To know the life-long educational implication in Out of School Education. The result of this study can be concluded that the out-of-school education based on lifelong education is oriented towards the challenges and behaviors of learners toward maturity. The writer found there are three stages of implementation of the concept of Long Life Education in Islam, lifelong education in a family environment, lifelong education in formal education, and lifelong education in non-formal education. The lifelong educational implications of PLS exist with programs that are oriented towards Education and Writing, Vocational Education, Professional Education, Education toward Change and Development.